Haemosiderosis as a Consequence of Haemolysis and Repeated Blood Transfusion following Arsenic Intoxication in a Child - Afroze, Ainun; Rukunuzzaman, M; Hasan, S; Rahman, A (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Arsenic is a ubiquitous element detected in low concentration virtually in all environmental media. Arsenic intoxication may occur following ingestion, inhalation or contact. A 5 1/2 years old girl with arsenic intoxication and haemosiderosis was admitted in the department of Paediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University. In Bangladesh 54 out of 64 districts are affected by arsenic contamination in tubewell water. 35 million people are at risk of arsenic toxicity. This patient presented with history of repeated blood transfusion since 4 months of age associated with fever, Jaundice and abdominal pain. She also had anaemia and hepatosplenomegaly. She had high arsenic level in urine and hair samples. Haemosiderosis was diagnosed by liver biopsy. She was treated with Desferrioxamine, antioxidant vitamins (Vit A, E), zinc and blood transfusion. In the present case haemolysis due to arsenic intoxication occurred at an early age, for which frequent blood transfusions were needed. Multiple transfusion without proper chealation led to development of haemosiderosis. DOI: 10.3329/jbcps.v26i3.4200 J Bangladesh Coll Phys Surg 2008; 26: 149-152